Abundance and seasonal distribution of the Southern North Carolina estuarine system stock (USA) of common bottlenose dolphins (Tursiops truncatus) - Silva, Daniela (J. Cetacean Res. Manage., 2020)
ABSTRACT Under the U.S. Marine Mammal Protection Act, bottlenose dolphins [Tursiops truncatus] along the United States Atlantic coast are managed as a series of 17 distinct stocks. To determine the status of each stock, the Potential Biological Removal (PBR) is compared with anthropogenic removals, primarily as a result of fisheries bycatch. Estimates of abundance, with associated measures of variance, are required to generate the PBR for each stock. The objectives of the current study were to estimate abundance for the Southern North Carolina Estuarine System Stock (SNCESS) of bottlenose dolphins and to refine the southern boundary of this stock. To meet these objectives, photo-identification surveys were conducted during the summer and winter of 2014 in estuarine and nearshore coastal waters in southern North Carolina. The surveys extended 25km south of the defined southern stock boundary, along the northern South Carolina coast. One mark and one recapture survey were conducted for each season. Each survey was completed in four or five days and covered over 300km of survey tracklines. Dorsal fin images were processed and managed using FinBase, and only images of suitable quality and distinctiveness were used for estimates of abundance. A three-step decision tree was used to assign each dolphin group to either the SNCESS or an adjacent coastal stock, based on sighting location, ranging patterns derived from matches to photo-identification catalogs, and statistical modeling. Only sightings classified as SNCESS were used to estimate stock abundance. Abundance estimates were calculated using three methods: the Chapman modification to the Lincoln-Petersen method, package Rcapture in Program R, and program MARK 6.2. The most parsimonious estimate was generated using the package Rcapture for program R, with the bias corrected M0 model yielding an estimate of 283 dolphins (CV = 0.33, 95% CI 170-396) in the summer of 2014. The distribution of SNCESS dolphins shifted south in the winter and several individuals were observed up to 70km southwest of the currently recognized southern boundary. The results of this study support the current definition of the SNCESS but suggest revisions to the southern boundary. The SNCESS is the smallest bottlenose dolphin stock off the east coast of the USA and is at risk of population decline as a result of fisheries-related mortality.